2017
DOI: 10.5205/1981-8963-v11i12a22917p5339-5353-2017
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção da infecção pelo zika vírus nas gestantes

Abstract: RESUMOObjetivo: avaliar as competências dos ACS no desenvolvimento das atribuições esperadas e definidas pelo Ministério da Saúde nas ações de pré-natal de risco habitual, desenvolvidas no âmbito da ESF, em relação à prevenção da infecção pelo zika vírus na gestação. Método: estudo quantitativo, descritivo, transversal, com coleta de dados em 14 equipes da Estratégia de Saúde da Família, mediante um questionário com três partes: A (enfrentamento ao Aedes aegypti); B (pré-natal de baixo risco) e C (medidas de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Similar studies have shown that providing care to children with neurological problems reduces maternal health levels (29)(30)(31)(32)(33)(34) . The loss of self-care is associated with the fact that they are solely responsible for the demands of the family, the socioeconomic status of these women was also a limiting factor for the establishment of healthy behaviors, such as minimally adequate food and intervals of sleep and rest.…”
Section: Discussionmentioning
confidence: 78%
“…Similar studies have shown that providing care to children with neurological problems reduces maternal health levels (29)(30)(31)(32)(33)(34) . The loss of self-care is associated with the fact that they are solely responsible for the demands of the family, the socioeconomic status of these women was also a limiting factor for the establishment of healthy behaviors, such as minimally adequate food and intervals of sleep and rest.…”
Section: Discussionmentioning
confidence: 78%